On the Basement of Canadian Greenstone Belts - Gilkson, A. (Geoscience Canada, 1978)
Summary The elucidation of the nature of the crust which originally underlay and delimited Archean volcanic-sedimentary greenstone belts is essential for the under-Standing of the early Precambrian crustal record - and through it of early terrestrial evolution. Stratigraphie evidence from the Pilbara and Yilgarn cratons in Western Australia is consistent with data from the eastern Transvaal, Rhodesia and southern India, suggesting a fundamental dichotomy of major greenstone sequences. Two assemblages are recognized, including: 1 ) early greenstones which predate, and occur as xenoliths within, the isotopically oldest granites in each craton, and 2) late greenstones, which overlie the early greenstones through major paraconfor-mities accompanied by thick chert and acid volcanic units, and may in places overlap the early granites unconformably. The early granites typically consist of tonalité and granodiorite whose geochemical and isotopic parameters indicate derivation from parental basic materials. In this article, the possible relevance of these observations to the question of granite-greenstone relations in the Canadian Precambrian Shield is considered, with particular attention to the Archean crustal foundation of Keewatin (Abitibi) and Yellowknife greenstone belts.